Risk Perceptions and Psychological Effects During the Italian COVID-19 Emergency - Lanciano, Tiziana; Graziano, Giusi; Curci, Antonietta; Costadura, Silvia; Monaco, Alessia (Frontiers in Psychology, 2020)
The current study provides data about the immediate risk perceptions and psychological effects of the COVID-19 pandemic among Italian participants. A sample of 1034 volunteers answered a web-based survey which aimed to investigate the many facets of risk perceptions connected to COVID-19 (health, work, economy, social and psychological), and risk-related variables such as knowledge, news seeking, perceived control, efficacy of containment measures, and affective states. Socio-demographic characteristics were also collected. Results showed that although levels of general concern are relatively high among Italians, risk perceptions are highest with regards to the economy and work, and lowest concerning health. Cognitive and affective risk-related variables affected the several risk perception domains differently. COVID-19 knowledge did not affect any risk perception while the perceived control decreased health risk likelihood. The other risk-related variables amplified risk perceptions: News seeking increased work-economy risk; efficacy of containment measures increased all perceived risks; negative affective states of fear, anger and sadness increased health and psycho-social risks; anxiety increased only health risk, and uncertainty increased work-economy and psycho-social risk perceptions. Finally, positive affective states increased health risk perception. Socio-psychological implications are discussed.